THE INFLUENCE OF ROA, ROE, AND NPM ON PRICE BOOK VALUE - Apip Apip; Clara Yully Diana Ekaristi (Jurnal Ipteks Terapan, 2023)
This research aims to test the influence of Return on Assets, Return on Equity, and Net Profit Margin on Price Book Value. There were 30 manufacturing companies registered in Indonesian Stock Exchange during 2019-2021 which become samples of this research. It used double linier regression as analysis method. The results of this research show that Return on Asset variable significantly influence on Price Book Value with value of 0.042. the analysis result of Return on Equity with value of 0.369 and Net Profit Margin with value of 0.139 do not significantly influence the Price Book Value. Keywords: net profit margin, price book value, return on asset, return on equity.